Comparative Study of The Patient Satisfaction In Vali-Asr and Amir-Aalam Hospitals Based on Pivotal Core Peripheral (PCP) Model - Zahedi; Mehri (Iran University of Medical Sciences, 2009)
Background and Aim : Rapid changes in the environment have exerted significant pressures on hospitals to incorporate patient satisfaction in their strategic stance. Both academicians and managers are interested in discovering how patients form their satisfaction levels and behavioral intentions. One of the developed models for measuring patient satisfaction is known as Pivotal Core Peripheral (PCP) attributes that has been applied in this research.   Material and Method: A descriptive survey was carried out in 2006. The population was patients of Amir-Aalam and Vali-Asr hospitals affiliated to Tehran University of Medical Sciences and Health Services. The sample consisted of 500 patients selected through convenience sampling. A questionnaire was developed based on Pivotal Core Peripheral attributes model. Cranach's Coefficient Alpha rendered the reliability of the questionnaire as 0.98. Data were gathered and analyzed by SPSS using descriptive and inferential statistics .   Results: Mean values for pivotal, core, and peripheral variables were, respectively 4.45, 4.33, and 4.10 for Vali-Aasr hospital, and 4.57, 4.50, and 4.21 for Amir-Aalam hospital. A statistical significant difference was seen between the mean scores of core attributes of patients in 2 hospitals.   Conclusion: Although the mean score in three areas in two hospitals were more than the test value (i.e. 3.5), upgrading the quality of variables with lower mean scores is recommended.